Odpowiedzi

2010-03-14T13:57:58+01:00
1. a)4(a+b)
b)3(x+5y)
c)7(x+2y)
d)17(x-1)
e)b(c-d)
f)x(y-3)
g)p(y-1)
h)y(9x-1)
i)b(a+3b)
2010-03-14T13:58:02+01:00
A) 4a+4b = 4(a+b)
b)3x+15y = 3(x+5y)
c)7x+14y = 7(x+2y)
d)17x*-17 = 17(x²-1)
e)bc-bd = b(c-d)
f)xy-3x = x(y-3)
g)py-p = p(y-1)
h)9xy-y = y(9x-1)
i)ab+3b* = b(a+3b)

2 Wyłącz przed nawias jednomian 2x
a)2x-2xy = 2x(1-y)
b)4x-8xy = 2x(2-4y)
c)6x*-12x = 2x(3x-6)
2010-03-14T13:58:28+01:00
1
a) 4a+4b= 4(a+b)
b)3x+15y=3(x+5y)
c)7x+14y=7(x+2y)
d)17x²-17=17(x²-1)
e)bc-bd=b(c-d)
f)xy-3x=x(y-3)
g)py-p=p(y-1)
h)9xy-y=y(9x-1)
i)ab+3b²=b(a+3b)
2
a)2x-2xy=2x(1-y)
b)4x-8xy=2x(2-4y)
c)6x²-12x=2x(3x-6)